Tourist product: JMZ agüita de coco - Ascencio Sánchez, Zulma Amanda
JMZ Agüita de coco is an idea that was born from a group of three guys who want to modernize and implement a new way of consuming and marketing something unique that is the fruit of the coconut palm. This project was born to be large and recognized for providing an excellent product in the area of the department of La Libertad, El Salvador. This project is thought to be a good place where to go, relax and enjoy a wonderful and healthy drink that is the coconut water, also it is thought to be an amazing place to share a good time with family and friend. The project is thought to be in La Libertad, El Salvador, where National and international people can enjoy our product, a product 100% Salvadoran one. This location where our project will be located is excellent because it is a place where to drink a fresh and delicious coconut water is a need. The project name is JMZ Agüita de coco is because it is wanted to be something original from El Salvador and the acronym JMZ means the names of the three of the three creators of this project. The idea of this project is to offer an original and healthy product produced in the same place where it will be sold and at the same time to show that this location is very productive and it offers a lot of. This project is tempted to be an amazing one for national and international tourists, and whenever Highway to Surf City is named, our project will be a reference on this place. As a conclusion, the project is about the selling a well-known product that is Coconut water but it will be sell in a way everybody wants to buy it and share with family, friends and alone also.